IDENTIFYING MENTAL HEALTH FACTORS OF CANCER PATIENTS IN HOSPITAL X: Identifikasi Faktor-Faktor Kesehatan Mental pada Pasien Kanker di Rumah Sakit X - Rochana Ruliyandari; Solikhah Solikhah; Fatma Nuraisyah; Wulan Rahmadhani (Jurnal Berkala Epidemiologi, 2023)
Background: Physical health of people living with cancer causes mental health disorders and unknowingly affects the overall quality of patients' life. As many as 34.40% of cancer patients in Indonesia experience depression due to anxiety and fear. Objective: Therefore, this study was conducted to determine the mental health of cancer patients in the hospital so that the relationship between the mental health of cancer patients and other factors, such as the characteristics of the respondents, family support, and spirituality, is known. Methods: The type of research for this study is quantitative with a cross-sectional design using the Pearson Chi-Square analysis. There were 96 respondents in this study who were cancer patients from Hospital X. The independent variables used were the respondent's demographic characteristics (age, gender, occupation, and education), family support, and spirituality, with the dependent variable being mental health (stress and depression). Results: The results of the study showed that cancer patients had the latest elementary school education (40.60%), status not working (61.50%), female (66.70%), early elderly (35.40%), 70.80% received moderate family support, 76% had moderate spirituality, 51% experienced moderate stress, and 57.30% had depression. The characteristics of respondents in this study, namely gender, education, occupation, and spiritual factors, were not associated with mental health in cancer patients. Conclusion: The results showed that age and family support were factors associated with the mental health of cancer patients, while other demographic characteristics (gender, occupation, and education) also spiritual factors were not associated with the mental health of the cancer patients.